Synergistic effects of climate change and habitat fragmentation on species range shifts and metapopulation persistence - Frederico Mestre (Frontiers of Biogeography)
The effects of climate and landscape change on biodiversity are relatively well described. However, there is limited understanding of the interactions between these processes, which generally operate at differing spatial scales. My objective was to evaluate the synergistic effects of climate and landscape changes on persistence and range shift dynamics. The model species was the Cabrera vole, Microtus cabrerae, a habitat specialist with limited dispersal ability. The present study demonstrated that, as a result of the combined effects of climate and landscape change, this species’ future potential distribution will be considerably reduced. The combined effect of climate change and landscape connectivity was assessed using the software MetaLandSim, a newly developed package, with a good balance between data requirements and output quality, allowing researchers to account for connectivity and dispersal in range forecasting. With this R package, the species’ metapopulational dynamics could be simulated at the landscape scale, and range expansion for different connectivity scenarios could be computed.